2022
DOI: 10.3390/nu14102092
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Supplementation Hinders the Role of Exercise Training as a Natural Activator of SIRT1

Abstract: Exercise training (ET) is a natural activator of silent mating type information regulation 2 homolog 1 (SIRT1), a stress-sensor able to increase the endogenous antioxidant system. SIRT1 activators include polyphenols and vitamins, the antioxidant properties of which are well-known. Antioxidant supplements are used to improve athletic performance. However, they might blunt ET-related benefits. Middle-distance runners (MDR) taking (MDR-S) or not taking antioxidant supplements (MDR-NoS) were compared with each ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Plasma levels have been reported to be lower in established cases of HFpEF [24], and it is considered a potential mediator of age-related cardiovascular diseases [25]. It is shown to play an important role in the development of cardiac hypertrophy, fibrosis and inflammation, all of which are pathophysiological mechanisms underlying HFpEF, likely through its link to the renin-angiotensin aldosterone system [24,26]. Collectively, this needs to be confirmed in further longitudinal and interventional studies.…”
Section: Discussionmentioning
confidence: 98%
“…Plasma levels have been reported to be lower in established cases of HFpEF [24], and it is considered a potential mediator of age-related cardiovascular diseases [25]. It is shown to play an important role in the development of cardiac hypertrophy, fibrosis and inflammation, all of which are pathophysiological mechanisms underlying HFpEF, likely through its link to the renin-angiotensin aldosterone system [24,26]. Collectively, this needs to be confirmed in further longitudinal and interventional studies.…”
Section: Discussionmentioning
confidence: 98%
“…However, we do not think that the type and workload might have influenced the variables measured since all participants were refrained from exercising at least 24 h before the measurements. Recently, Sellitto et al [ 68 ] reported that antioxidant supplementation may hinder the Role of exercise training as a natural activator of sirtuin 1 (SIRT1) which is activated by polyphenols antioxidants. On the other hand, highly trained endurance athletes did not benefit from consuming nitrate-rich foods but might have benefited from polyphenol consumption [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the beneficial effects of monoterpenes mediated by SIRT1 activation, namely increased cellular antioxidant capacity and improved mitochondrial biogenesis, may be hindered by the antioxidant properties that many of those compounds also present [ 120 ]. Indeed, it was shown that treatment with antioxidant vitamins abrogates or, at least, blunts the beneficial effects of calorie restriction and exercise training [ 121 ], two interventions well-known to increase SIRT1 and ameliorate aging and related diseases [ 122 , 123 ]. In agreement with the concept of mitohormesis, increasing evidence suggests that a small degree of oxidative stress may be required to potentiate the antioxidant response and improve bioenergetics so that the presence of an exogenous source of antioxidants eliminates the drive to activate the endogenous response to challenging conditions, such as exercise training and calorie restriction, which includes and is mediated, at least in part, by SIRT1.…”
Section: Discussionmentioning
confidence: 99%